Di-Block PLCL and Tri-Block PLCLG matrix polymeric nanoparticles enhanced the anticancer activity of loaded 5-fluorouracil - Ashour, Abdelkader Elbadawy Abbas; Badran, Mohamed M.; Kumar, Ashok; Rishi, Arun K.; Yassin, Alaa Eldeen Bakry (IEEE, 2016)
In the current study, 5-FU-loaded nanoparticles (NPs) were prepared using polylactic-co-glycolic acid (PLGA), polycaprolactone (PCL), di-block poly lactide-co-caprolactone (PLCL) and tri-block poly L-lactide-co-caprolactone-co-glycolide (PLCLG). The influence of these polymers on the particle sizes, morphology, drug loading, and in vitro drug release was investigated. The anticancer activity was assessed utilizing MTT assay in three human cancer cell lines of different tissue origin; brain (Daoy), liver (HepG2), and colorectal (HT29) using suitable negative and positive controls. The prepared NPs showed a uniform spherical shape with an average size range of 193.5± 6.3 to 303.5± 3.3 nm with negative zeta potential. The entrapment efficiency achieved with F4-F6 (block copolymer NPs) was 78-79% and significantly higher compared with F1 PLGA (31%) and F2; PCL (37%). An initial rapid 5-FU release followed by a slow release ranging from 35% to 81% after 72 h was observed. All the prepared NPs formulations showed enhancement in the cytotoxicity of 5-FU towards all the three cancer cell lines. Generally, block copolymer NPs (F4-F6) showed higher % cell death over PLGA (F1) and PCL (F2) NPs after 48 and 72 h incubation in the case of HepG2 and HT-29. The incorporation of PEG with the tri-block (F6) caused a significant increase in the cytotoxicity of NPs in all of the three cancer cell lines. Block copolymer-based NPs can be considered as promising carriers for enhancing the efficacy of 5-FU in cancer therapy.